EFEKTIVITAS PIJAT ENDORPIN DAN PIJAT BREASTCARETERHADAP KELANCARAN PRODUKSI ASI PADA IBU NIFAS DI RSU PKU MUHAMMADIYAH DELANGGU - Endang Wahyuningsih; Wiwin Rohmawati (INVOLUSI: Jurnal Ilmu Kebidanan, 2019)
The puerperium (puerperium) is the period after the discharge of the placenta until the reproductive organs recover like before pregnancy and normally the postpartum period lasts for 6 weeks or 40 days. Problems in breastfeeding include mastitis, breast abscess, breast milk dams, blisters Inward nipple, swollen breasts, blocked ducts, irritated nipples and the baby refuses to feed. The purpose of this study was to determine the effectiveness of endiorpine massage on the smooth production of breast milk in postpartum mothers at PKU Muhammadiyah Delanggu Hospital. The research method used is quantitative research with a cross sectional approach. Quasy-experimental research design with pre-post-test design was non equivalent with control group design. The population in this study were all post-partum mothers in PKU Muhammadiyah Delanggu Hospital, amounting to 174 people. The research sample was taken by 40 people who met the inclusion criteria in July. Sampling was with Accidental Sampling. The research results of endorphin massage and breastcare massage on the smooth production of breast milk in postpartum mothers were 28 (70%). The conclusion in this study shows that endorphin massage is effective for smooth production of breast milk in post-partum mothers at PKU Muhammadiyah DelangguHospital compared to breastcare massage with the results of 28 respondents (70%). Suggestions for postpartum mothers are able to apply endorphin massage and breastcare massage at home using endorphin massage and breastcare massage.